Structural and Functional Characteristics of Microplastic Associated Biofilms in Response to Temporal Dynamics and Polymer Types - Tu, Chen; Liu, Ying; Li, Lianzhen; Li, Yuan; Vogts, Angela; Luo, Yongming; Waniek, Joanna J. (Bulletin of environmental contamination and toxicology, 2021)
The colonization of bacterial communities and biofilm formation on microplastics (MPs) have aroused great concern recently. However, the influence of time and polymer types on the structural and functional characteristics of biofilms remains unclear. In this study, three types of MPs (polyethylene, polypropylene, and polystyrene) were exposed for different time periods (10, 20 and 30 days) in seawater using a microcosm experiment. Microscopic spectroscopy and high-throughput gene sequencing techniques were used to reveal the temporal changes of structural and functional characteristics of MPs associated biofilms. The results indicate that the biofilm formation is affected by both the incubation time and the polymer type. In addition, bacterial diversity and community structure in the biofilms show selectivity towards seawater, and tend to shift over time and among different polymer types. Moreover, biofilms are shown to harbor plastic degrading bacteria, leading to the changes of functional groups and surface hydrophobicity, and thereby enhancing the biodegradation of MPs.